Avaliação do impacto da esplenectomia na recuperação das contagens de plaquetas em pacientes com púrpura trombocitopênica idiopática no Hospital São Lucas da PUCRS - Romanov, Jalise Wolski de Oliveira (2020)
Introduction: the Idiopathic Thrombocytopenic Purpura (ITP) is described as plaquetopenia, without another definitive cause, mediated by lysis of IgG autoantibodies that enter into the plasma membrane and are destroyed by macrophages of the endothelial reticulum tissue, mainly from the spleen. The diagnosis is defined by clinical history, physical examination and hemogram distinguish by isolated thrombocytopenia. Treatment depends on its clinical presentation and platelet counts, and from monitoring the patient until an emergency, including splenectomy. Objective: this study aimed at demonstrating the importance of splenectomy in the treatment of ITP that does not respond to drug treatment, evaluating the response to short- term and long-term splenectomy, with platelet counts of 24 hours after the procedure, after 6 months and after 5 years. Method: the following values were considered as response criteria: complete response in peripheral blood, over 100.000 /mm3 platelets; partial response, platelets above 30.000/mm3 absolutely and or 30.00/mm3 platelets added to the presplenectomy value; non-response to the surgical procedure, considered as not increasing the number of platelets, considering levels after splenectomy below 30.000/mm3 platelets. Finally, the loss of response to the surgical procedure was evaluated, considered a decrease in platelet counts below the level reached in the immediate response, in the period of 6 months and 5 years. Data was submitted to ANOVA, Mann-Whitney testing and Pearson’s chi-squared statistical analysis, according to the studied variables, with 5% level of significance. Results: splenectomy provided a significant enhance in platelets number in periphery blood even after 5 years from its performance and this enhance in the first 24 hours tends to maintain practically constant within the following 6 months. However, after 5 years, it was possible to observe a significant reduction in the number of platelets in peripheral blood, although the values are still superior when compared to those pre-splenectomy. Complete response was found in 82.26% of the patients and partial response in 17.74%. Statistical tests revealed that not age of the patient at the time of diagnosis (p=0.56), nor time occurred between the disease’s diagnosis and the performing of splenectomy (p=0.69), nor the number of platelets in periphery blood before the procedure (p=0.07) influenced in the type of response to the procedure (complete or partial). The gender of the patient did not influence the type of response either (p=0.79). Conclusion: splenectomy was efficient in refractory cases of IPT.